Bacillus subtilis Inoculation Improves Nutrient Uptake and Physiological Activity in Sugarcane under Drought Stress - da Fonseca, Mariley de Cássia [UNESP]; Bossolani, João William [UNESP]; de Oliveira, Sirlene Lopes [UNESP]; Moretti, Luiz Gustavo [UNESP]; Portugal, José Roberto [UNESP]; Scudeletti, Daniele [UNESP]; de Oliveira, Elisa Fidêncio [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (MDPI, 2022)
Sugarcane (Saccharum spp.) is one of the most important crops in the world. Throughout the sugarcane’s growth stages, periods of drought are common, causing detrimental effects on plant growth. Therefore, the search for strategies for minimizing the impact of drought on sugarcane development is of great interest. Plant growth-promoting bacteria hold the potential for improving tolerance to drought in agricultural systems. Thus, the present study aimed to evaluate whether inoculation with Bacillus subtilis can reduce the negative effects of drought on the nutritional, physiological, and morphological characteristics of sugarcane plants. For this, sugarcane was cultivated in a greenhouse, under controlled conditions of water and temperature, with the aid of four treatments: without and with inoculation of B. subtilis, in normal conditions of water availability, and in conditions of water restriction (2 × 2 factorial), with four replications. In treatments with inoculation, the pre-emerged seedlings were immersed in a B. subtilis solution and transplanted into experimental pots. Our results showed that inoculation with B. subtilis improved plant nutrition and chlorophyll concentrations. As a result, the gas exchange parameters (especially net photosynthetic rate and water use efficiency) were also improved, even under drought conditions. In addition, stress parameters (antioxidant metabolism activity) were reduced in inoculated plants. The sum of these beneficial effects resulted in increased root growth, tillering, stalk weight, and higher sucrose concentration in the stalks.
Keywords: antioxidant enzymes; net photosynthetic rate; plant growth-promoting bacteria; water restriction